Kualitatif KONFLIK BATIN TOKOH DALAM PERSPEKTIF PSIKOANALISIS DALAM DRAMA “AKU DAN HIDUPKU” - Hagai Panjaitan; Vina Merina Br. Sianipar; Renandha Siburian; Enjel Hutapea; Selvia Situmeang; Syntia Sihombing (Jurnal Lazuardi, 2026)
This study aims to investigate the inner conflict of the protagonist in the drama Aku dan Hidupku by M. Alfin Zubaidi and colleagues using a psychoanalytic approach according to Sigmund Freud. In this drama, there is the character of Farid, a 15-year-old boy who is struggling with leukemia and facing various mental stress due to lack of attention from his family. The methodology applied in this study is a qualitative descriptive approach with a focus on psychoanalysis, which explores the structure of the character's psyche based on Freud's three main pillars: id, ego, and superego. Primary data sources come from the drama text Aku dan Hidupku, while secondary data include literature relevant to psychoanalytic theory and drama studies. The research findings show that the character of Farid is involved in a complex inner conflict between the drives of the id (the desire for affection, denial of the disease he suffers), ego (Farid's reaction to social reality), and superego (moral awareness strengthened by interactions with the spirit of Karina). This conflict culminates in a psychological change of the character from a state of despair to an understanding of the meaning of life. This study confirms that the drama script Aku dan Hidupku is rich in psychological elements that can be studied more deeply using Freud's psychoanalytic theory.